Dental fractures: types, causes, and treatment - Bamofleh, Samar A.; Alotaibi, Alanoud F.; Alshahrani, Aidel A.; Alahmadi, Shoroug M.; AlHumaidan, Abdulaziz I.; Abomelha, Sarah A.; Alkheshail, Walaa A.; Almuhaydib, Rayyanah N.; Zafer, Roaa M.; Alkahtani, Khloud M.; Albeladi, Bashayer T. (International Journal Of Community Medicine And Public Health, 2022)
Studies indicate that the management of dental fractures might be challenging because many cases present with minor, hard-to-discover traumas, requiring extensive evaluation and diagnostic procedures. Accordingly, adequate management can only be achieved by establishing a proper diagnosis, drawing an adequate treatment plan, and conducting regular follow-up appointments. We have discussed the different causes, types, and treatments of dental fractures. The commonest causes include impaction by trauma, whether direct or indirect. Many traumatic events were reported in the literature, and age and carious lesions are important factors to consider. Many types of dental fractures were also reported in the literature, including root fractures, crown root fractures, enamel-dentin fractures with and without pulp exposure or crown fractures, enamel infractions, and fractures. Other types include avulsion, intrusion, extrusion, lateral luxation, concussion or subluxation, splinting, and alveolar segment fractures. The treatment should be integrated based on the fracture type, and adequate follow-up should be established to achieve the best predictive outcomes.